A new galago species for South Africa (Primates: Strepsirhini: Galagidae). - (:unkn) unknown (My University, 2016)
The primate fauna of South Africa has historically been viewed as comprising three diurnal cercopithecoid taxa — chacma baboons (Papio ursinus), vervet (Chlorocebus pygerythrus) and samango monkeys (Cercopithecus albogularis) — and two nocturnal lorisoid species — the thick-tailed greater galago (Otolemur crassicaudatus) and the southern lesser galago (Galago moholi). Here we report the positive identification of a third galago species within South Africa's borders: the Mozambique dwarf galago or Grant's galago, Galagoides granti (Thomas and Wroughton, 1907). The taxon was previously held to be restricted to Mozambique, eastern Zimbabwe, Malawi and Tanzania, but we have also observed it in the sand forest of Tembe Elephant Park and the Tshanini Community Reserve, near the Mozambique border. The species was formerly mistaken for Galago moholi, erroneously (we believe) extending the range of the latter species into northern KwaZulu-Natal. In South Africa the two small galagos are unlikely to have overlapping ranges: Galago moholi prefers dry savanna woodlands, whereas Galagoides granti is apparently confined to dry sand forest. However, both species may coexist with the larger and more widespread Otolemur crassicaudatus, an inhabitant of moist savanna, forest edge and thicket. The true South African ranges of both small galago species need to be ascertained.
Keywords: African Research